The role of prefrontal catecholamines in attention and working memory - Clark, Kelsey L.; Noudoost, Behrad (Frontiers in Neural Circuits, 2014)
While much progress has been made in identifying the brain regions and neurochemical systems involved in the cognitive processes disrupted in mental illnesses, To date, the level of detail at which neurobiologists can describe the chain of events giving rise to cognitive functions is very rudimentary. Much of the intense interest in understanding cognitive functions is motivated by the hope that it might be possible to understand these complex functions at the level of neurons and neural circuits. Here, we review the current state of the literature regarding how modulations in catecholamine levels within the prefrontal cortex alter the neuronal and behavioral correlates of cognitive functions, particularly attention and working memory.